Development of HOTS and TPACK Based Learning Media on Parabola Material - Pamungkas, Sugeng Adi; Panggabean, Ellis Mardiana; Irvan, Irvan (Universitas Ma'arif Lampung, 2024)
This research aims to: 1) find out how HOTS and TPACK-based learning tools work on parabola material; 2) find out how effective the HOTS and TPACK-based learning tools are in the parabolic equation material being developed; 3) find out how students respond to the application of HOTS and TPACK-based learning tools in the parabolic equation material being developed. This research is development research. The development model used in this research is the Thiagarajan 4-D development model, namely the define, design, develop, and disseminate stages. The results of the research show that: 1) it was declared valid in terms of the validity results by experts who stated that the learning tools consisted of: (1) the average validation results of the learning implementation plan (RPP) were 4.34, (2) the average validation results the average Student Worksheet is 4.24, (3) the average validation result of the HOTS ability test is 4.17; 2) The developed HOTS and TPACK based learning tools have met the specified effectiveness criteria in terms of: (1) In trial II, 90.4% (19 students) completed the learning; (2) Achievement of learning objectives has been achieved for each question item in trial II, namely question number 1 at 84.76% and question number 2 at 84.29%; (3) student responses in trial II were 94%; and (4) the learning time used does not exceed the normal learning time set by the school and 3) the increase in HOTS thinking skills, namely Trial I, was 52.4% or the 11 students who completed it had experienced an increase in Trial II to 90.4% or 19 students completed..